Nice Work de David Lodge : Un « Condition of England novel » des années 1980 ? - Armelle Parey (Revue LISA)
In Nice Work, David Lodge appropriates the model of the « condition-of-England novel » which he transposes into the 1980s. More than a mere transposition, Nice Work turns out to be an open rewriting of the Victorian novels quoted in epigraphs since the text, with its comical aspect and its auto-reflexive dimension, distances itself from realism. Far from being innocent, this rewriting considers critically the Thatcher era as well as contemporary literary theory and gives a discerning homage to Victorian novels.